Persepsi dan Partisipasi Masyarakat terhadap Local guide di Desa Ohoidertawun dan Desa Ohoililir - Ngamelubun, Maria Magdalena; Hukubun, Wiwien Gaby (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
Local Guide has an important role in the development of tourism in the region. Hence, they should have good English skills in order to explain or provide information about the area. Besides, a local guide should also have insight or skill in tour guiding so that they can be able to guide tourists who visit the area. The location of this study is in Ohoi Ohoidertawun and Ohoi Ohoililir. This study is conducted from April to October 2017. This study uses descriptive qualitative method. Data collection technique is conducted by using questioner, interview and documentation. The results of this study which based on the distribution of participation and perception shows that Local Guide owned by local tourism ohoi is still 'less' in terms of communicating using English as an international language to communicate with foreign tourists. Thus, the Local Guide is still required to obtain English tourism training and guiding tour techniques.